DEVELOPMENT OF CHARACTER EDUCATION COMIC BOOKS REFERRING TO CARIYĀPITAKA FOR CLASS VII BUDDHIST EDUCATION - Karuna, Nanda; Suranto, Suranto; Parsiyono, Parsiyono (Jurnal Pencerahan, 2023)
One of the problems in the education is lack of supporting media in implementing character education in the classroom. Based on the issue, the objectives of this research are (1) To produce a tested product in the form of a character education comic book that refers to Cariyāpitaka; (2) Knowing the feasibility of character education comic books that refer to Cariyāpitaka which are developed based on the ADDIE development model. This research is a development research (R&D) with the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used include observation, interviews, and documentation. The data credibility is assessed by using transferability, dependability, and confirmability techniques. The data analysis technique used for qualitative data is data reduction, data presentation, and conclusion. The results obtained in this study are in the form of character education comic books that refer to Cariyāpitaka which are suitable for use as a learning media. The feasibility level is shown by the validation results from material experts who give an assessment of 90%, which means that the product is in the very good category, then the assessment given by media expert 1 is 83.3% and from the media expert 2 is 86.6% with a very good category too. The effectiveness of the product developed is 89.23% based on the results of distributing questionnaires to students, so that the product developed is categorized as very feasible and effective as a medium for a character education learning.